Pemodelan Agradasi Degradasi Dasar Sungai Konaweha Hilir menggunakan Hec-Ras 6.4.1 Sulawesi Tenggara - Widiawati Rustan; Hadi Khardana; Agus Santoso (Departement of Mathematics Education, 2024)
The Konaweha River is one of the valuable natural resources in the Southeast Sulawesi region. This river not only serves as a vital water source for the community but also harbors a rich river ecosystem, playing a crucial role in maintaining environmental balance. Analysis related to flow characteristics and sedimentation is essential in formulating flood adaptation and mitigation measures. However, such analyses have been limited in important rivers in Indonesia, including the Konaweha River in Konawe Regency, Southeast Sulawesi. Therefore, this study aims to analyze changes in the riverbed elevation over a 10-year period from 2021 to 2030 due to sedimentation under daily discharge conditions. This research serves as a case study for sedimentation analysis through Sediment Transport Modeling. The modeling results indicate that the Konaweha River has the potential for Aggradation and Degradation. Based on sediment transport modeling, the Konaweha IV section (upper reaches) is dominated by Aggradation, while the Konaweha II and Konaweha III sections (middle reaches) show a tendency of both degradation and aggradation, with stability. In contrast, the Konaweha I section (lower reaches) is dominated by degradation, even though the riverbed elevation does not experience a significant increase during the period from 2021 to 2030. The total volume of aggradation and degradation over the 10-year period is 1,488,306 tons and 1,181,249 tons.